The effectiveness of exercise interventions to prevent shoulder injuries in sport: a systematic review and meta-analysis - Swart, Johannes Jacobus Wessel (My University, 2021)
Background: The literature supports exercise interventions to avert injuries in the lower extremity as well as injuries in general. Nevertheless, the utilisation of exercise strategies to prevent sports-related shoulder injuries remain unproven. This systematic review’s primary aim is to evaluate the effectiveness of exercise interventions to prevent shoulder injuries in athletes. Aims: Primarily, this review collated and summarised the available evidence on shoulder injury prevention in sport. The first secondary aim is to provide acute versus overuse injury estimates. The second secondary aim is to designate and classify the exercise interventions applied to the upper extremity into strength, flexibility, mobility, plyometrics, proprioception, functional or multimodal exercises. The third secondary aim is to describe and categorise the identified upper extremity components of exercise interventions into open kinematic chain exercises or closed kinematic chain exercises. Methods: An extensive multi-database search was performed. No language or publication restriction was applied. Twelve databases were searched from inception up until November 2020. The search identified fifteen (15) eligible studies that were included and critically appraised. Data extraction and synthesis followed the Joanna Briggs Institute Reviewer’s Manual for Systematic Reviews of Effectiveness and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The data was synthesised utilising the JBI System for the Unified Management, Assessment and Review of Information to produce several meta-analyses. Results: The pooled results indicated a statistically significant result with moderate heterogeneity in favour of the application of exercise interventions to prevent shoulder injuries [0.77 (0.65 – 0.91) RR, 95% CI, P = 0.013]. An analysis of upper extremity injury shows a smaller effect and with substantial heterogeneity [0.65 (0.56 - 0.77) RR, 95% CI, P = 0]. Heterogeneity was fully resolved with the removal of poor methodological studies and reveals a larger statistically significant effect [0.56 (0.38 - 0.82) RR, 95% CI, P = 0.002]. Subgroup analysis revealed a slightly greater effect for acute shoulder injuries [0.75 (0.58 – 0.96) RR, 95% CI, P = 0.024] compared to overuse injuries [0.75 (0.58 – 0.96) RR, 95% CI, P = 0.024]. Shoulder-specific programmes showed a statistically insignificant and inferior effect [0.85 (0.72 - 1.01) RR, 95% CI, P = 0.067]. v The varieties of exercise interventions applied to the upper extremity consisted of 20% strength, 6% flexibility, 11% mobility, 9% plyometrics, 7% proprioception, 27% functional and 20% multimodal exercises. 56% of shoulder exercises performed was classified as closed kinetic chain exercises. Conclusion: This systematic review with meta-analysis supports and advocates for the use of exercise interventions to prevent shoulder injuries in sport. The programmes utilised can prevent both acute and overuse shoulder injuries with a slightly greater prophylactic effect in acute injuries. Exercise interventions designed to address the shoulder specifically were not superior to programmes targeting the shoulder incidentally. Future researchers are encouraged to attain higher internal validity levels by reducing biases, improving shoulder specific programmes, and utilising a superiority trial design.
A research report submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021